0361 PennPALS: An Innovative, Bidirectional Text Messaging System Using PAP Usage Data to Increase Patient Adherence with PAP Therapy. (25th May 2022) - Jimenez, David; Cadman, Sara; Watach, Alexa; Khan, Neda; Hahn, Lauren; Bae, Charles
Abstract: Introduction: Cloud-based systems that collect PAP data provide patients and providers with near real-time usage information, but a system that identifies/intervenes with patients at risk of PAP non-adherence has not been available to date. The Penn PAP Automated Learning System (PennPALS) is an automated, bidirectional text messaging system that uses PAP data to initiate text messaging conversations to patients in a timely manner. Methods: PennPALS was created using Way to Health, an evidence-based patient engagement platform, to leverage PAP data, such as daily average hours of use and time spent with a large mask leak, to identify and initiate automated text messages to help patients troubleshoot issues. Depending on their responses, patients were given a pre-defined recommendation via text or escalated to a clinical provider contacting them via phone-call. Two 30-day pilots were conducted, which collectively enrolled 33 patients who were prescribed PAP for the first time. Results: Most patients were White, Non-Hispanic (54.8%, n=17), males (64.5%, n=20), with a mean age of 52 years. Two patients did not receive a PAP machine by the end of the pilot. PennPALS engaged patients via text message 115 times. Of the 31 patients who started PAP, 7 (22.6%) were adherent from the start of enrollment and only received positive enforcement text messaging. Across the 24 (77.4%) patients that experienced issues, there were 58 text message conversations, which resulted in 32 clinical escalations. Twenty-one (67.7%) patients triggered text messaging interventions for using PAP for < 4 hours/night on average over a 7-day period or experiencing a large mask leak, n=10 (32.3%) and n=11 (35.5%) respectively. At 30-days, 17 (70.8%) of the 24 patients were adherent (i.e. using their PAP at least 4 hours/night on average over the last 7-days). Patient feedback was generally favorable with a Net promoter score (likelihood to recommend) of 68.4 (n=19). Conclusion: PennPALS effectively identified/intervened with patients at risk of non-adherence to PAP therapy, and the bidirectional text messaging system helped patients become adherent in the first 30 days of treatment. Further testing and longer-term monitoring is needed to examine the effectiveness of PennPALS on long-term PAP adherence. Support (If Any):